LIBRARY PROMOTION IN INCREASING VISITORS AT LIBRARY OF TANJUNGBALAI CITY - Yuma, A. Adnan Rasyidi; Dalimunthe, Muhammad; Naldo, Jufri (PERSPEKTIF: Journal of Social and Library Science, 2023)
The research that has been carried out is entitled "Regional Library Promotion in Increasing Visitors to the Tanjungbalai City Regional Library" where what will be studied in this research is the promotion carried out, the supporting and inhibiting aspects of the promotion, the strengths and weaknesses of the promotion carried out, things The aim is to increase library visitors. The research methodology uses a qualitative research approach. In this research, social case study research was used. This means that researchers conduct studies or analyze a social problem that occurs or is related to the general public. The data sources in this research are the results of interviews, related documents and observations. Resource persons were selected based on their positions and duties in carrying out library functions and several visitors they met during the research. Data collection techniques using interviews, document study and observation. Data is processed by reducing data, presenting data and drawing conclusions. The results of the research explain that (1) the Tanjungbalai Regional Library carries out various promotions to increase visitors, (2) The biggest obstacle in implementing promotions is related to funds and lack of personnel (3) The advantage of promotions is not in the activities, but in the persistence of the assigned personnel ( 4) Even though it is not large, the promotion carried out can be considered to have increased visitors to regional libraries. Based on the research findings above, in carrying out its functions,